Blended Inquiry Learning with Ethno-STEM Approach for First-Semester Students' Chemical Literacy - Sumarni, W.; Sumarti, S. S.; Kadarwati, S. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
Chemical literacy, one of the most important aspects of chemistry teaching and learning, has been paid more attention. However, chemistry learning has not focused much on providing students with learning experiences that could improve chemical literacy. Ethno-STEM approach-integrated inquiry-based learning has been reported as an effective learning model in the chemistry learning. This study aims to analyze the effectiveness of blended inquiry learning with an ethno-STEM approach in improving students’ chemical literacy. This study used a quantitative descriptive approach with a one-shot case study design. Ninety-four first-semester students participating in the General Chemistry course (3 credits) in the teacher education program were involved in the study. During the study, blended inquiry learning with an ethno-STEM approach was applied to the participating students for one semester. Questionnaires, descriptive questions, and interviews were used to collect the research data. A descriptive statistic was used to analyze the data. This study showed that the blended inquiry learning with the ethno-STEM approach was effective to improve the students’ nominal and functional chemical literacy but ineffective to increase conceptual and multidimensional literacy. The students’ prior knowledge in chemistry played an important role in the growth of chemical literacy. A continuing BIL-ethno-STEM in chemistry teaching and learning would allow a significant improvement in the conceptual and multidimensional literacy.